Effect of Different Doses of Rabbit Manure on the Abundance, Growth Rate and Production of Zooplankton in Plurispecific System for Fish Larvae Feeding - LIADY, MOUHAMADOU NOUROU DINE; ADANDE, Richard; FIOGBE, EMILE DIDIER; SOSSOUKPE, EDMOND (My University, 2017)
In order to determine the optimal dose of rabbit manure for plurispecific production of fresh water zooplankton in controlled area, the effects of six different doses of dry rabbit manure (T1 = 300 g/m3, T2 = 600 g/m3, T3 = 900 g/m3, T4 = 1200 g/m3, T5 = 1500 g/m3, T0 = 0g/m3) on physico-chemical and biological parameters of areas were monitored for 27 days in cultures realized in plastic buckets of 80 L capacity each. Manures are from rabbits fed with diet previously revealed favorable to their growth, and is made of 2% of dried cassava, 30% of maize bran, 10% of palmist cake, 10% of soya cake, 5% of cotton cake, 2% of shell, 10% of malt, 5% of beer yeast, 10% of Panicum maximum and 1% of salt. Six days after fertilization, buckets were seeded with zooplankton by 26 individuals per liter (ind/L). Results obtained show that the supply of rabbit manure has improved chemical properties and microalgae production (phytoplankton) with treatments T1, T2, T3, T4 and T5. Optimal conditions of zooplankton production through phytoplankton are obtained with doses in T2 and T4 which present the best specific growth rate. The daily production through the highest phytoplankton biomass (chlorophyll-a) has been obtained with dose in T5. Thus, doses 600 g/m3 and 1200 g/m3 of rabbit manure may be considered optimal for a plurispecific production of fresh water zooplankton. It was noted that Rotifers were predominant in abundance in almost the different culture areas.
Keywords: Rabbit manure; Optimal dose; Zooplankton; Plurispecific production